2014
DOI: 10.1113/jphysiol.2013.264929
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive agonists exert dynamic and coordinated effects on vascular smooth muscle cell elasticity, cytoskeletal remodelling and adhesion

Abstract: Key pointsr This study demonstrates rapid and dynamic changes in adhesion and cell elasticity following agonist stimulation that culminate in a remodelled cytoskeleton in vascular smooth muscle.r Evidence is presented that the changes in adhesion and elasticity are coordinated and that these variables demonstrate temporal oscillation consisting of three major oscillation components.r Eigen-decomposition spectrum analysis revealed that these components of oscillation in cell elasticity and adhesion may be linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 44 publications
5
71
0
2
Order By: Relevance
“…Conversely, the VSMC stiffness level may be influencing the adhesion properties, as recently published work supports a mechanistic link between, stiffness and adhesion. Hong et al 43,44 demonstrated that treatment of VSMCs with the vasoactive agents angiotensin II or adenosine, respectively increase and decrease VSMC stiffness and adhesion in a coordinated manor. It may be that the interplay of these two mechanisms, VSMC stiffness and VSMC adhesion, contributes to the interaction of hypertension and aging in accelerating vascular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the VSMC stiffness level may be influencing the adhesion properties, as recently published work supports a mechanistic link between, stiffness and adhesion. Hong et al 43,44 demonstrated that treatment of VSMCs with the vasoactive agents angiotensin II or adenosine, respectively increase and decrease VSMC stiffness and adhesion in a coordinated manor. It may be that the interplay of these two mechanisms, VSMC stiffness and VSMC adhesion, contributes to the interaction of hypertension and aging in accelerating vascular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) nanoindentation was performed as previously described to estimate the elastic modulus (stiffness) of individual myocytes (15,35,36). In brief, cardiomyocytes were applied to laminin-coated dishes for 40 min and then washed 3 times in nominally Ca 2ϩ -free PSS at 22-25°C.…”
Section: Atomic Force Microscopy Nanoindentation Of Intact Cardiomyocmentioning
confidence: 99%
“…For instance, VSMC dysfunction changes the adhesive interactions with the ECM during active relaxation and contraction. Moreover, modulation of the elasticity of the cortical cytoskeleton occurs in parallel with changes in VSMC adhesion properties [20, 21]. Further, modulation of the elasticity of the cortical cytoskeleton occurs in parallel with changes in VSMC adhesion properties [20, 21].…”
Section: Dysregulation Of Vascular Cells and Extracellular Matrix In mentioning
confidence: 99%
“…Moreover, modulation of the elasticity of the cortical cytoskeleton occurs in parallel with changes in VSMC adhesion properties [20, 21]. Further, modulation of the elasticity of the cortical cytoskeleton occurs in parallel with changes in VSMC adhesion properties [20, 21]. Angiotensin II (Ang II) induces VSMCs to synthesize collagen, fibronectin, ECM proteins, as well as activation of the ECM-modifying MMPs [16].…”
Section: Dysregulation Of Vascular Cells and Extracellular Matrix In mentioning
confidence: 99%